A taxonomy of explanations in a general practitioner clinic for patients with persistent "medically unexplained" physical symptoms. Issue 2 (February 2017) - Morton, LaKrista; Elliott, Alison; Cleland, Jennifer; Deary, Vincent; Burton, Christopher
Highlights: Explaining persistent "medically unexplained" symptoms to patients is difficult. A new taxonomy describes symptom explanations by type and content. Different types of explanation carry different implications for patients. This taxonomy provides a template for developing and testing explanations. Abstract: Objective: To develop a taxonomy of explanations for patients with persistent physical symptoms. Methods: We analysed doctors' explanations from two studies of a moderately-intensive consultation intervention for patients with multiple, often "medically-unexplained, " physical symptoms. We used a constant comparative method to develop a taxonomy which was then applied to all verbatim explanations. Results: We analysed 138 explanations provided by five general practitioners to 38 patients. The taxonomy comprised explanation types and explanation components. Three explanation types described the overall structure of the explanations: Rational Adaptive, Automatic Adaptive, and Complex. These differed in terms of who or what was given agency within the explanation. Three explanation components described the content of the explanation: Facts – generic statements about normal or dysfunctional processes; Causes – person-specific statements about proximal or distal causes for symptoms; Mechanisms – processes by which symptoms arise or persist in the individual. Most explanations conformed to one type and contained several components . Conclusions: This novel taxonomy for classifying clinical explanations permits detailed classification of explanation types and content. Explanation types appear to carry different implications of agency. Practice implications: The taxonomy is suitable for examining explanations and developing prototype explanatory scripts in both training and research settings.